2016
DOI: 10.1017/s1744552316000240
|View full text |Cite
|
Sign up to set email alerts
|

Judging in lower courts: Conventional, procedural, therapeutic and feminist approaches

Abstract: Recent theorising about feminist judging has concentrated on appellate courts and their judgments. This paper develops a conceptualisation of feminist judging in lower, first instance courts, which are dominated by high case volume and limited time for each matter, with decisions given orally and ex tempore rather than in elaborated written judgments. Through careful accounts of the philosophy, goals and practices of conventional as well as newer, more engaged approaches to judging, the paper compares and cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 91 publications
(137 reference statements)
0
12
0
2
Order By: Relevance
“…The law, particularly punishment, has often had detrimental consequences for defendants with mental disorders, including marginalization and oppression (King et al 2014). The therapeutic jurisprudence movement has attempted to remedy this in part by trying to help judges counteract their stereotyping and sanist tendencies in order to acknowledge that defendants with mental disorders have unaddressed problems of which they can be helped to "overcome" with attention and therapeutic treatment provided by the court (Hunter et al 2016). Rather than believing the defendant should attune their behavior to regulations set by punishments based on traditional social-control, therapeutic judges must motivate offenders to engage in treatment and develop therapeutic plans to reduce criminal behavior (Wiener et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The law, particularly punishment, has often had detrimental consequences for defendants with mental disorders, including marginalization and oppression (King et al 2014). The therapeutic jurisprudence movement has attempted to remedy this in part by trying to help judges counteract their stereotyping and sanist tendencies in order to acknowledge that defendants with mental disorders have unaddressed problems of which they can be helped to "overcome" with attention and therapeutic treatment provided by the court (Hunter et al 2016). Rather than believing the defendant should attune their behavior to regulations set by punishments based on traditional social-control, therapeutic judges must motivate offenders to engage in treatment and develop therapeutic plans to reduce criminal behavior (Wiener et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…First, one such way to integrate such biases into therapeutic judging may be reorienting the concept of therapeutic jurisprudence as a form of social control to judges. Although therapeutic jurisprudence implicitly adopts a model of an offender being "sick" and requiring treatment provided by the court, this authority is still based on social control, while also providing treatment (Hunter et al 2016). The treatment provided within the therapeutic process still operates as a form of regulation over the offender's criminal behavior by understanding and treating such behavior through a judge's legal authority (Moore 2006).…”
Section: Discussionmentioning
confidence: 99%
“…La présence de logiques binaires dans une décision portant sur le harcèlement sexuel traduit des attitudes, des valeurs et des croyances dans l’esprit du décideur qui ont pu influencer l’ensemble de l’audition et, plus particulièrement, l’appréciation de la preuve, l’évaluation de la probité des témoignages, et ultimement, le sort de la réclamation (Hunter, Roach Anleu et Mack 2016). Par conséquence, les résultats de notre recherche appellent à une rectification de la situation pour les travailleuses harcelées sexuellement au travail dont le recours exclusif est une réclamation en vertu de la LATMP.…”
Section: Resultsunclassified
“…Dans cette conception traditionnelle du système juridique, le décideur doit faire preuve de détachement et d’impartialité : « This conventional judge is disembodied, objective, unemotional and impersonal. Law, fact and reason are the legitimate sources for judicial decisions… When applying law, personal views, biases, values and emotions should be set aside … » (Hunter, Roach Anleu et Mack 2016, 340).…”
unclassified
“…The recent feminist judgment projects (Douglas et al, 2014a;Enright et al, 2017;Stanchi et al, 2016;Women's Court of Canada, 2006), and theorizing around them (e.g. Davies, 2012;Fitz-Gibbon and Maher, 2015;Hunter, 2008Hunter, , 2010Hunter, , 2012Hunter, , 2013Hunter, , 2015aHunter, , 2015bHunter et al, 2016;Rackley, 2012), have identified a variety of practices which might be identified as 'feminist' judging. One key insight from these projects is that a feminist approach is at least as, if not more, likely to be found in judicial reasoning than in the outcome of a case.…”
Section: Positive Endorsement Of Legislative Reformmentioning
confidence: 99%